2014
DOI: 10.7555/jbr.28.20140029
|View full text |Cite
|
Sign up to set email alerts
|

Rab proteins implicated in lipid storage and mobilization

Abstract: Abnormal intracellular accumulation or transport of lipids contributes greatly to the pathogenesis of human diseases. In the liver, excess accumulation of triacylglycerol (TG) leads to fatty liver disease encompassing steatosis, steatohepatitis and fibrosis. This places individuals at risk of developing cirrhosis, hepatocellular carcinoma or hepatic decompensation and also contributes to the emergence of insulin resistance and dyslipidemias affecting many other organs. Excessive accumulation of TG in adipose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 102 publications
(116 reference statements)
2
15
0
Order By: Relevance
“…Treatment with iodothyronines induced a decrease in the expression of both Rab18 and TIP47. Rab18 is a LD-coating GTPase, whose role in lipid metabolism is still under debate, but it seems to be involved in basal lipogenesis and TAG accumulation (Kiss and Nilsson, 2014 ). Recently, several Rab proteins have been localized to LD surface, and some works revealed that GTP is a key mediator of LD-mitochondria interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with iodothyronines induced a decrease in the expression of both Rab18 and TIP47. Rab18 is a LD-coating GTPase, whose role in lipid metabolism is still under debate, but it seems to be involved in basal lipogenesis and TAG accumulation (Kiss and Nilsson, 2014 ). Recently, several Rab proteins have been localized to LD surface, and some works revealed that GTP is a key mediator of LD-mitochondria interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Rab proteins, as key regulators of membrane trafficking, are involved in LD interactions (Murphy et al, 2009 ). Among the Rab family, LD-associated Rab18 plays a crucial role in the vesicle trafficking between LDs and other organelles (such as mitochondria, peroxisomes, endoplasmic reticulum (ER)) and regulates LD quantity and diameter by controlling fusion/fission processes (Stenmark, 2009 ; Kiss and Nilsson, 2014 ). It is now accepted that storage and release of FFAs from LDs result from variations in the expression and/or activity of PLIN proteins and associated lipases.…”
Section: Introductionmentioning
confidence: 99%
“…This consistent observation has not been fully investigated and remains an intriguing paradox of CLD biology. Several hypotheses have been proposed to address this issue including the role of CLDs as sequestration sites [ 59 , 60 ] or in the regulation of membrane trafficking [ 61 ]. The identification of non-lipid related protein in the CLD fraction has expanded our perception of the CLD from a simple lipid storage site to a complex and multi-functional organelle [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the decreasing rate among the groups, PV and MPV had more significant decrease than CON; while there was no difference between PV and MPV. The reason is believed to be the decrease in body fat quantity and blood lipid in PV and MPV, in the view of existing studies as follows: the increase in cytokine secretion by excessive storage of body fat [ 60 ] and the decrease in proinflammatory cytokine secretion accompanied by the decrease in blood triglyceride [ 61 ].…”
Section: Discussionmentioning
confidence: 99%